Exploring the Needs of Female Afghan Migrants Living in Japan - Nakanishi, Yol (Asean Social Work Journal, 2022)
This paper explores the needs of Afghan women living in Chiba, Japan through participatory observation, a co-organized health seminar, and in-depth interviews with Afghan women and relevant stakeholders.It became clear that the women's needs were mainly related to finding their place in Japanese society, such as making Japanese friends and having paid jobs, and acquiring the tools to go to places such as hospitals and city halls by themselves. Here, the Japanese language skills often seemed to be at the root.Iconclude that the Japanese government and the local municipality fail in providing systematic support to meet the needs of Afghan women, and that they rely too much on volunteer-based organizations. Structural systems of local volunteer organizations and Japanese institutions such as hospitals contribute to the maintenance of traditional gender norms of the community, and make it difficult for women to find a place in Japanese society and to exercise their agency. The strength and drive of Afghan women andthe already established trusted relationship with Japanese channels show that there is a high potential for successful social integration of this group when appropriate support is made available, which will eventually improve their wellbeing